2022
DOI: 10.1371/journal.pone.0277945
|View full text |Cite
|
Sign up to set email alerts
|

The combination of chronic stress and smoke exacerbated depression-like changes and lung cancer factor expression in A/J mice: Involve inflammation and BDNF dysfunction

Abstract: Objective Depression is positively correlated with the high incidence and low survival rate of cancers, while more cancer patients suffer depression. However, the interaction between depression and cancer, and possible underline mechanisms are unclear. Methods Chronic unpredictable mild stress (CUMS) was used to induce depression, and smoke to induce lung cancer in lung cancer vulnerable AJ mice. After 8 weeks, sucrose preference and forced swimming behaviors were tested. Blood corticosterone concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Chronic stress-induced depression-like behaviors are also associated with neuron apoptosis in mPFC and amygdala [24,25]. We found that KLK8 de ciency signi cantly attenuated CUMS-induced apoptosis in mPFC (supplemental Fig.…”
Section: Transgenic Overexpression Of Klk8 Exacerbates Whereas Klk8 D...mentioning
confidence: 71%
“…Chronic stress-induced depression-like behaviors are also associated with neuron apoptosis in mPFC and amygdala [24,25]. We found that KLK8 de ciency signi cantly attenuated CUMS-induced apoptosis in mPFC (supplemental Fig.…”
Section: Transgenic Overexpression Of Klk8 Exacerbates Whereas Klk8 D...mentioning
confidence: 71%
“…Chronic stress-induced depression-like behaviors are also associated with neuron apoptosis in mPFC and the amygdala [ 24 , 25 ]. We found that KLK8 deficiency significantly attenuated CUMS-induced apoptosis in mPFC (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Similar mechanisms were indicated by experiments in mice with lung cancer. 32 Alcohol exposure regulates gut microbiota and mediates anxiety and depression through NLRP3-mediated neuroinflammation. 33,34 This analysis not only illuminates the potential mechanisms affecting mental well-being but also provides valuable insights for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 Similar mechanisms were indicated by experiments in mice with lung cancer. 32 Alcohol exposure regulates gut microbiota and mediates anxiety and depression through NLRP3‐mediated neuroinflammation. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%